Evaluation of strontium-containing hydroxyapatite as bone substitute in sheep tibiae. - Gomes Machado, Callinca Paolla; Vaz Braga Pintor, Andrea; Calasans Maia, Mônica Diuana (Brazilian Journal of Implantology and Health Sciences, 2019)
With the advancement of research in biomaterials, it has been suggested that the best osteoconductivity of hydroxyapatite would be achieved if its crystal were closer to the structure, size and morphology of biological apatite, that is why nano-hydroxyapatite (nano-HA) is of great importance. current interest. Strontium ions are known to reduce bone resorption, induce osteoblastic activity and stimulate bone formation. The aim of this study was to evaluate biocompatibility and osteoconduction in surgical defects filled with nano-hydroxyapatite microspheres containing 1% strontium (nano-SrHA), stoichiometric nano-HA microspheres (nano-HA) compared to the clot (control) . Four Santa Inês sheep, weighing an average of 32 kg, were anesthetized and submitted to three 2 mm diameter perforations in the medial face of the tibia. The surgical defects were filled with blood clot, microspheres of Sr-HA 1% and microspheres of HA. After 30 days the samples were drawn (6 mm), decalcified, processed for inclusion in paraffin and stained with hematoxylin and eosin (HE) for histological evaluation with light microscopy. All groups revealed bone neoformation from the periphery to the center of the defect, with the nano-SrHA group being less intense among those studied. Presence of a discrete mononuclear inflammatory infiltrate in all experimental groups. Giant foreign body cells were only observed in the HA group. Areas of bone neoformation were observed in close contact with both biomaterials. According to the results obtained, microspheres of HA and SrHA 1% are biocompatible and have osteoconductive properties.